2019
DOI: 10.1186/s13046-019-1303-z
|View full text |Cite
|
Sign up to set email alerts
|

Flubendazole demonstrates valid antitumor effects by inhibiting STAT3 and activating autophagy

Abstract: Background Signal transducer and activator of transcription 3 (STAT3) is an oncogene, which upregulates in approximately 70% of human cancers. Autophagy is an evolutionarily conserved process which maintains cellular homeostasis and eliminates damaged cellular components. Moreover, the STAT3 signaling pathway, which may be triggered by cancer cells, has been implicated in the autophagic process. Methods In this study, we found that the anthelmintic flubendazole exerts p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 27 publications
(35 reference statements)
2
48
0
1
Order By: Relevance
“…Mechanistically, flubendazole may also target NF-κB signaling, which is required for esophageal squamous carcinoma cell survival 17 . In colorectal and breast cancer cells, flubendazole exerts anti-tumor and anti-metastatic activities by inhibiting STAT3 22 , 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, flubendazole may also target NF-κB signaling, which is required for esophageal squamous carcinoma cell survival 17 . In colorectal and breast cancer cells, flubendazole exerts anti-tumor and anti-metastatic activities by inhibiting STAT3 22 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the context, it may positively or negatively influence cancer metastasis 48 , which is ultimately the primary cause of cancer-associated mortality. A number of studies have indicated a close relationship between flubendazole and autophagy, though the exact mechanism has been not characterized, especially in the context of TNBC 22 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Table 1 ( 4 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 ) summarizes the antitumorigenicity of benzimidazole anthelmintics on cancer cell lines. Benzimidazole anthelmintics inhibit the progression of cancer through a variety of mechanisms.…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Camentioning
confidence: 99%
“…Mebendazole had no effects on normal fibroblasts compared with adrenocortical carcinoma cells ( 79 ). The inhibitory effect of flubendazole was limited in normal human liver cells and cardiomyocytes compared with colorectal cancer cells ( 34 ). Fenbendazole showed little effect on normal human bronchial epithelial cells, normal immortalized human prostate cells, and primary mouse fibroblasts compared with lung cancer cells, as the IC50 values for fenbendazole were several fold higher in these normal cells compared with cancer cell lines ( 38 ).…”
Section: Antitumorigenic Effects Of Benzimidazole Anthelmintics In Camentioning
confidence: 99%
“…Accordingly, tumor cell populations exposed to MC-inducing agents are likely to respond with a significant degree of heterogeneity including the appearance of several cell phenotypes whose relative proportions and fates may ultimately reflect the evolutionary status and the nature of the particular tumor [ 77 , 78 , 79 ]. Thus several research groups have reported that tumor cells exposed to benzimidazoles in vitro become polyploid, aneuploid or senescent, upregulate autophagy and die via apoptosis or necrosis [ 80 , 81 , 82 ]. In Figure 1 , two possible scenarios of benzimidazole-exposed GBM cells responses are shown including cell morphologies as well as select molecular players.…”
Section: Mitotic Catastrophementioning
confidence: 99%